Pendampingan Ekonomi Pesantren Melalui Sentralisasi Transaksi Cost makan Santri di Pondok Pesantren Nurul Jadid Paiton - Yaqin, Ainol; Arifin, Maknunatun Navisah; Umami, Zaimatul; Ruqoyyah, Siti; Novitasari, Dwi Anggraini; Sulistyawati, Ika (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
In one of the efforts to increase the economic progress of the pesantren and also to eat for the students, especially at the Nurul Jadid Boarding School, Probolinggo, it is very necessary to have a centralized program for paying the cost of paying for the cost of the students’ meals so that each student’s meal is regelated and even becomas a way of saving the cost of living for the students. For decades, the Nurul Jadid Islamic Boarding School has not been able and succeeded ini centralizing the cost of food for students and processed food products for students at one door. The centralization of the santri staple food business is believed by the pesantren. The fear of pesantren in managing this business is quite an obstacle, but by providing location, technology and human resources, pessntren is expected to be able to maintain and preserve Costmara’s business. Our service uses a Consultation approach, where wa several individuals at the same time assist, guide and direct policy makers, employees and servants at Nurul Jadid Cost of Eating student to make this businenss lively and comfartable, especially able to nourish the economy of the Pesantren and serve the needs of the santri so that the pesantren achieves the peak of independence and economic sovereignty. Centralization of the cost of meals for studentswas initiated by Pesantren bereau and ini teh end it was acquired by the business bereua, Centralized peyments at the santri supplies simpab office and food management in public kitchens with a sufficient number of employess, centralization of santri food and payments were able to mave the pesantren economy for more beneficial interests including religious agends, education, health, equipment and others within the Nuru Jadid Islamci Boarding School. Economics is the foundation of every pesantren agenda. So Cost Mara contributes a lot the economic pace of Islamic Boarding Schools. Santru obtain sufficient benefits, including low prices, healthy composition and savings for santri and the ecomic flow santri guardiens.